Kekuatan Pembuktian Alat Bukti Keterangan Terdakwa Dalam Persidangan Online - I Nyoman Budiana; I Gede Gatot Kasmariadi (Jurnal Hukum Saraswati, 2024)
law enforcement officers. Trials usually held face-to-face in the courtroom have changed to online via video conference due to the implementation of health protocols to maintain distance. The defendant and the defendant's legal advisor in several cases refused online trials. The problem in this research is the strength of evidence and legal certainty of the defendant's testimony in online trials. There are several things that form the basis, including the Criminal Procedure Code, criminal case evidence, criminal law evidentiary theory, legal certainty theory and online trials. This research chooses to use normative juridical research methods through a statutory approach (The Statute Approach). Legal materials come from secondary data collected using the Snow Balls Method and then sorted into primary, secondary and tertiary legal materials. The results of this research are that the evidence of the defendant's statement provided electronically has the same strength as an offline trial and the legal certainty of the defendant's statement in the online trial is guaranteed by statutory regulations. Online meetings provide an expanded interpretation of space that is not limited to direct physical face-to-face meetings but also face-to-face in cyber/virtual worlds, not limited by distance and place. The laws and regulations governing the Supreme Court provide space to establish Supreme Court Regulations to regulate Criminal Procedure Law when these provisions are not yet regulated in the Criminal Code.